Decatenation checkpoint‐defective melanomas are dependent on PI3K for survival. (23rd June 2014) - Brooks, Kelly; Ranall, Max; Spoerri, Loredana; Stevenson, Alex; Gunasingh, Gency; Pavey, Sandra; Meunier, Fred; Gonda, Thomas J.; Gabrielli, Brian
Summary Melanoma cell lines are commonly defective for the G2‐phase cell cycle checkpoint that responds to incomplete catenation of the replicated chromosomes. Here, we demonstrate that melanomas defective for this checkpoint response are less sensitive to genotoxic stress, suggesting that the defective cell lines compensated for the checkpoint loss by increasing their ability to cope with DNA damage. We performed an siRNA kinome screen to identify kinases responsible and identified PI3K pathway components. Checkpoint‐defective cell lines were three‐fold more sensitive to small molecule inhibitors of PI3K. The PI3K inhibitor PF‐05212384 promoted apoptosis in the checkpoint‐defective lines, and the increased sensitivity to PI3K inhibition correlated with increased levels of activated Akt. This work demonstrates that increased PI3K pathway activation is a necessary adaption for the continued viability of melanomas with a defective decatenation checkpoint.